Analysis Of Errors In Writing Hijaiyyah Connecting Letters In Grade 2 At MI Ma'arif Bego Sleman Yogyakarta - Fatur Fahrezi; Alfina Wardah; Syafira Hadya (IAIN Bone, 2026)
Writing hijaiyyah letters is a fundamental skill in Arabic language learning, particularly at the Madrasah Ibtidaiyyah (MI) level. Grade 2 students at MI Ma’arif Bego experienced difficulties in writing connected hijaiyyah letters correctly, including errors in letter position, form, connection, and harakat, which may alter word meanings. This descriptive qualitative study aims to identify the types and causes of these errors. Data were collected through observations of students’ worksheets, interviews with Arabic teachers, and documentation of students’ written work. The findings reveal four major error types: letter position, letter form and connection, harakat and layout, and letter separation. The novelty of this study lies in integrating orthographic error analysis with the perspectives of Arabic morphology (Sharaf) and word derivation (Isytiqaq), demonstrating how elementary writing errors affect morphological structure and lexical meaning. The errors were mainly caused by students’ limited understanding of connected-letter rules and insufficient writing practice. The study recommends intensive writing exercises, the use of posters, lined exercise books, and hijaiyyah letter cards, as well as systematic classroom practice to improve students’ Arabic writing skills.